Estrogen receptor β activation impairs prostatic regeneration by inducing apoptosis in murine and human stem/progenitor enriched cell populations. - Shirin Hussain (Public Library of Science (PLoS), 2012)
Androgen depletion is the primary treatment for prostate disease; however, it fails to target residual castrate-resistant cells that are regenerative and cells of origin of prostate cancer. Estrogens, like androgens, regulate survival in prostatic cells, and the goal of this study was to determine the advantages of selective activation of estrogen receptor β (ERβ) to induce cell death in stem cells that are castrate-resistant. Here we show two cycles of short-term ERβ agonist (8β-VE2) administration this treatment impairs regeneration, causing cystic atrophy that correlates with sustained depletion of p63+ basal cells. Furthermore, agonist treatment attenuates clonogenicity and self-renewal of murine prostatic stem/progenitor cells and depletes both murine (Lin(-)Sca1(+)CD49f(hi)) and human (CD49f(hi)Trop2(hi)) prostatic basal cells. Finally, we demonstrate the combined added benefits of selective stimulation of ERβ, including the induction of cell death in quiescent post-castration tissues. Subsequent to castration ERβ-induces further apoptosis in basal, luminal and intermediate cells. Our results reveal a novel benefit of ERβ activation for prostate disease and suggest that combining selective activation of ERβ with androgen-deprivation may be a feasible strategy to target stem cells implicated in the origin of prostatic disease.